Relationship between Chinese children's imaginary companions and their understanding of second‐order false beliefs and emotions. (26th November 2018) - Lin, Qiyi; Zhou, Nan; Wan, Yingjia; Fu, Hong
Abstract : We investigated relationship between Chinese children's imaginary companions (ICs) and their understanding of second‐order false beliefs and emotions in 180 children, aged 5–6 years old. We examined the potential differences in second‐order false belief understanding and emotion understanding between children with and without ICs, children with egalitarian IC relationships and hierarchical IC relationships, as well as children with invisible friends and personified objects. The results revealed that children with ICs had better second‐order false belief understanding and emotion understanding than children without ICs. Compared with children with hierarchical relationships, children with egalitarian relationships had better second‐order false belief understanding. However, children with invisible friends and personified objects did not differ on their understanding of second‐order false beliefs and emotions. The results suggest that compared with IC types, IC status and child‐IC relationship qualities may be more relevant to children's theory of mind. It will be interesting for the future researchers to investigate the underlying mechanism of the differences between children with egalitarian IC relationships and hierarchical IC relationships.